PENGARUH KOMPOSISI LAPISAN NI-CR PADA BAJA ASME SA 210 C TERHADAP LAJU EROSI SUHU TINGGI - Utomo, Slamet Prasetyo; Darmadi, Djarot B.; Widodo, Teguh Dwi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The purpose of this study was to determine the high temperature erosion rate of the NiCr coating on ASME SA 210 C steel using the combustion oxy fuel thermal spray method. In Circulating Fluidized Bed (CFB) boiler, there is circulation of fly ash, silica sand and air in a high temperature environment which causes erosion. High temperature erosion can be minimized by using Ni-Cr alloy coating sing the combustion oxy fuel thermal spray method. NiCr alloy is proved a able to provider a metal alloy layer composition that can withstand temperatures of 600°C with a fly ash impact speed of 200m/s. The metal alloy compositions that have been studied are NiCr, NiCrCo, NiCrWc, NiCrWcCo, and NiCrCoMo. The results of this study indicates that metal alloys are generally atteche to the substrate and withstand at a high temperatures (600°C). The highest hardness provide by NiCrWcCo alloy which is 177.46 HV. The lowest hardness is found in the composition of the NiCrCo alloy (161.71 HV). The lowest high temperature erosion rate was found in the NiCrWcCo alloy, which was -0.00481 gram/minute. This low erosion rate because the NiCrWcCo alloy produces a good weeting effect for metal alloys and has a high hardness value.